Improving information security practices through computational intelligence - Awad, Wasan Shaker 1969-; El-Alfy, El Sayed M. 1968-; Al-Bastaki, Yousif A. Latif (A volume on Advances in information security, privacy, and ethics (AISPE) book series, 2016)
This book presents an overview of the latest and greatest research in the field, touching on such topics as cryptology, stream ciphers, and intrusion detection, and providing new insights to those working in computational intelligence, information security, and security engineering